Development of an Autonomous Robot for Competitive and Educational Purposes in the Sumo Category - Antunes, Bruna G.; Bezerra, Luiz F. F. P.; Canella, André L. C.; Pinto, Milena F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This article explores the design, construction, and performance of a robot designed to compete in the Mini Autonomous Sumo category. In this challenge, autonomous robots weighing up to 500 grams battle in a circular arena, being programmed to detect and push the opponent out of the combat area without human intervention. The nature of this competition requires the integration of various fields of knowledge, from the selection of components to the development of codes. By highlighting the challenges faced, the solutions adopted and the lessons learned, the article seeks to provide innovation in the area of competitive, educational, and interdisciplinary robotics.